2020
DOI: 10.1371/journal.pone.0239107
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage activity against and characterisation of avian pathogenic Escherichia coli isolated from colibacillosis cases in Uganda

Abstract: Avian Pathogenic Escherichia coli (APEC) cause colibacillosis leading to significant economic losses in the poultry industry. This laboratory-based study aimed at establishing stocks of avian pathogenic Escherichia coli lytic bacteriophages, for future development of cocktail products for colibacillosis management. The study determined the antibiotic susceptibility; phylogenetic categories, occurrence of selected serotypes and virulence genes among Escherichia coli stock isolates from chicken colibacillosis ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
(98 reference statements)
2
12
1
Order By: Relevance
“…Similarly, Merati et al [23] in Tiaret Province showed that E. coli strains were entirely resistant to NA and OFX (100%). Regardless, these findings disagreed with a previous report in Uganda [24], which showed lower resistance to CIP and NA at 20.02% and 60.70%, respectively. The significant resistance to quinolones could be due to the excessive use of these compounds, as they have widespread availability in the Algerian market at a low cost.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, Merati et al [23] in Tiaret Province showed that E. coli strains were entirely resistant to NA and OFX (100%). Regardless, these findings disagreed with a previous report in Uganda [24], which showed lower resistance to CIP and NA at 20.02% and 60.70%, respectively. The significant resistance to quinolones could be due to the excessive use of these compounds, as they have widespread availability in the Algerian market at a low cost.…”
Section: Discussioncontrasting
confidence: 99%
“…Messai et al [5] and Ibrahim et al [3] found high resistance to SXT at 82% and 95.50%, respectively. Resistance to CN, C, and NIT was higher than in Benameur et al [27], Halfaoui et al [19], Boutaiba Benklaouz et al [12], and Kazibwe et al [24]. The administration of these antibiotics is forbidden in veterinary medicine in Algeria.…”
Section: Discussionmentioning
confidence: 86%
“…The phage lysate obtained was plaque purified three times to produce a uniform phage stock. The isolated phages that could infect the APEC isolates from chickens that had died from colibacillosis were selected ( 4 ). Genomic DNA was extracted from the phages using 2% SDS and purified using a Qiagen Genomic-tip 100/G kit according to the manufacturer’s instructions.…”
Section: Announcementmentioning
confidence: 99%
“…100% among APEC isolates(Johnson et al 2008;De Oliveira et al 2015;Awawdeh 2018;Subedi et al 2018;Kazibwe et al 2020). This study along with others suggests that the ve genes used in the study are signi cantly associated to APEC isolates compared to non-APEC isolates(Johnson et al, 2008;Awawdeh 2018;Kazibwe et al 2020).…”
mentioning
confidence: 99%
“…100% among APEC isolates(Johnson et al 2008;De Oliveira et al 2015;Awawdeh 2018;Subedi et al 2018;Kazibwe et al 2020). This study along with others suggests that the ve genes used in the study are signi cantly associated to APEC isolates compared to non-APEC isolates(Johnson et al, 2008;Awawdeh 2018;Kazibwe et al 2020). The high prevalence of these ve genes which encode for various virulence traits suggests the pathogenic nature of APEC and these virulence genes (VGs) may be involved at different stages of infection in poultry birds.…”
mentioning
confidence: 99%